Mapping the spaces in-between: how ICT can assist in providing a safer and more efficient commuter experience for all - Enslin, Claire (School of Architecture, Planning and Geomatics, 2017)
Contemporary societies are facing rapid growth, urbanization and migration into the form of urban cities and environments. This requires the ever-expanding need for urban infrastructures to facilitate growing populations, communities and economies within cities. A vital elements within modern urban environments is the need for different forms of urban mobility in order to facilitate the movement and flow of people, goods and communication networks. Within the realm of urban mobility is the important aspect of public transport infrastructures as a system of creating more sustainable and equitable mobility for people within urban environments. Within cities of the global South, such as Cape Town, greater public transport systems are highly reliant on non-motorized transport (NMT) systems. This is due to issues of affordability, efficiency and spatial proximity of large portions of the population in relation to public transport facilities. Therefore, a substantial amount of urban mobility is facilitated by walking as a mode of transport. However, public transport within Cape Town are impacted by issues of personal safety. This is most visible in the Cape Town central business district (CBD). There is a lack of knowledge, design and planning around how people move within the city, and how NMT systems are used within the greater public transport domain. Issues of personal safety become the dominant focus for NMT and human-scale mobility within the city centre. This research examines these issues in more detail. In order to gain deeper knowledge around the experiences of NMT users within the CBD – a qualitative method of research was applied. The research used a gender-sensitive lens in order to gain an understanding as to how gender roles contribute to issues of personal safety and issues of mobility within the urban environment. The objective was to demonstrate the intersection of issues of personal safety within mobility and within space. The research is used as a foundation for creating a mobile phone App prototype. The design is based on user-generated data to create a tool that can help commuters find the safest human-scale mobility routes within the CBD. This tool demonstrates how ICT (information and communication technology) systems can be used to create safer mobility infrastructures and networks. The prototype relies on user-generated data that creates a platform for citizens to become planners in their everyday transport navigations. Thus the research also explores how technology and user-generated data can inform planning and urban management. This resulted in a tool that enables a cyclical system that blends the knowledge of the user and planner in the co-productive design of space and mobility infrastructures.